Can China's unified construction land market mitigate urban land shortage? Evidence from Deqing and Nanhai, Eastern coastal China. (April 2022) - Wen, Lanjiao; Chatalova, Lioudmila; Zhang, Anlu
Abstract: The continuing growth in demand for construction land in China along with the lagging capacity of government-controlled land supply call for solutions that could benefit both urban and rural development. The study analyzes whether opening up the rural construction land market in the course of establishing a unified land market can reduce shortage of urban construction land and associated urban land conflicts. Supply and demand functions of rural and urban construction land are estimated based on the first-hand and the second-hand data on official land transactions in Nanhai district and Deqing County, Eastern coastal China. The optimal land supply of local governments and rural collectives is determined assuming a Cournot-Nash duopoly equilibrium. The results show that a unified construction land market can improve efficiency of land transactions and substantially increase construction land supply. This effect is due to the complementary and substitutional relationship between the urban and rural land supply, where the former was found to be much stronger, especially in economically advanced areas. The observed substitution effect reflects along with the impact of the duopoly market the concurrent monopoly of local governments in coupon trading. The findings point out the relevance of establishing of the land market in different regions with different modes and inform other transition economies that are in the process of preparing or implementing land market reforms. Highlights: Land supply and demand functions are estimated for two study regions. Under duopoly conditions, a unified construction land market can mitigate urban land shortage. There coexist complementary and substitution effects between urban and rural land supply. The complementary effect is stronger than the substitution effect and increases with competition. The substitution effect reflects concurrent impacts of the duopoly and monopoly markets.